2006
DOI: 10.1177/0265407506064205
|View full text |Cite
|
Sign up to set email alerts
|

Embedded parenting? The influence of conjugal networks on parent–child relationships

Abstract: Data from a large survey of family functioning in Switzerland explore the extent to which various types of conjugal networks affect parenting and parent-child relationships (e.g., problems in assuming parental roles, parent-child disagreements, quality of parent-child relationships, and parental worries about the child). Results show that conjugal networks have significant indirect and direct effects on parent-child relationships but no buffering effect. Bicentric conjugal networks are singled out as indirectl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0
5

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 38 publications
(60 reference statements)
0
9
0
5
Order By: Relevance
“…Therefore, from their perspective, participants are under the care and scrutiny of a large number of interconnected family members from older generations. Intergenerational closure can have a positive influence on adolescent development (Furstenberg & Hughes, 1995), however, dense sets of kin relationships may have negative consequences such as amoral familism (Banfield, 1958), family interference (Johnson & Milardo, 1984;Widmer, Legoff, Hammer, Kellerhals, & Levy, 2006) or family overcare (Pyke & Bengston, 1996). Therefore, binding social capital within families may sometimes be detrimental to individual adaptation outside the family.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, from their perspective, participants are under the care and scrutiny of a large number of interconnected family members from older generations. Intergenerational closure can have a positive influence on adolescent development (Furstenberg & Hughes, 1995), however, dense sets of kin relationships may have negative consequences such as amoral familism (Banfield, 1958), family interference (Johnson & Milardo, 1984;Widmer, Legoff, Hammer, Kellerhals, & Levy, 2006) or family overcare (Pyke & Bengston, 1996). Therefore, binding social capital within families may sometimes be detrimental to individual adaptation outside the family.…”
Section: Discussionmentioning
confidence: 99%
“…By contrast, other work failed to find this expected associations (e.g., Ceballo & McLoyd, ). A possible explanation of these differences has been provided by the buffer hypothesis (Widmer, Le Goff, Levy, Hammer & Kellerhals, ) according to which social support may positively affect mental health, by buffering the negative effect of the stress, only under disadvantaged conditions. For example, mothers of preterm infants who benefit from a high level of social support in stressful circumstances, exhibit the most favorable patterns of parenting (Smith et al ., ).…”
Section: The Moderators Of the Transmission Processmentioning
confidence: 99%
“…employment, which plays a central role in father involvement and thus in coparenting). This broadening of the focus is legitimized by sociological studies that have demonstrated the influence of social variables on the quality of interactions in the family (Cochran & Niego, ; Widmer, Le Goff, Hammer, Kellerhals, & Levy, ). Although our study results suggest the importance of these broader variables, we did not assess them; further studies are thus needed to highlight the social determinants of parental cognitions.…”
Section: Discussionmentioning
confidence: 99%